Post-Implantation Syndrome Incidence After Secondary Endovascular Aortic Interventions - Tiago F. Ribeiro; Rita Soares Ferreira; Carlos Amaral; Frederico Bastos Gonçalves; Maria Emília Ferreira (EJVES Vascular Forum, 2025)
Objective: Post-implantation syndrome (PIS), a systemic inflammatory response following endovascular aneurysm repair (EVAR) is estimated to occur in approximately 30% of patients. It has been hypothesised to resemble a hypersensitivity reaction. A secondary exposure after a priming event could result in an altered risk and severity of PIS. This study aimed to determine the incidence and short-term clinical consequences of PIS after secondary endovascular aortic aneurysm interventions. Methods: Single centre retrospective observational study. Between 2011 and 2022, all consecutive patients who underwent secondary elective endovascular aortic interventions following a primary elective EVAR, thoracic endovascular aneurysm repair, or fenestrated and branched EVAR were considered. Re-interventions occurring within the first 30 post-operative days were excluded. PIS was defined as tympanic temperature ≥38°C and C-reactive protein (CRP) > 75 mg/L. Primary outcome was PIS incidence within three days. Secondary outcomes were short-term (30 days) outcomes and risk factors for PIS. Logistic regression analysis was performed to correct for confounders. Results: Seventy nine secondary interventions in 71 patients who underwent elective primary repair were analysed. During secondary repair, shorter stent graft combinations (median 305 vs. 171 mm, p ≤ 0.001) were implanted. In addition, patients were older (70 vs. 73 years, p = 0.043) and more frequently taking statin (79.4 vs. 92.2%, p = 0.026) or antiplatelet agents (66.7 vs. 85.6 %, p = 0.010). Overall, PIS occurred in 24.0%, significantly lower following secondary repair (32.3% vs. 16.5%, p = 0.022, adjusted odds ratio 0.38, 95% confidence interval 0.16–0.89). There were no significant differences in highest recorded temperature (p = 0.25), days of fever (p = 0.44), CRP, or peak white blood cell count. CRP presented a more delayed elevation in secondary PIS. Conclusion: After secondary endovascular aortic interventions, PIS incidence appears reduced compared with primary aortic repair. This should be interpreted with caution, in the context of procedural heterogeneity and limited number of cases. Further studies to confirm these findings and explore the underlying immunological mechanisms are required.